Knowledge and Attitudes of Dengue Virus Infection Transmission and Its Relationship with Eradication Action Program in Surabaya, Indonesia - Juliasih, Ni Njoman; Sucipto, Teguh Hari; Sari, Reny Mareta; Nuha, Zakiyathun; Soegijanto, Soegeng (Indonesian Journal of Tropical and Infectious Disease, 2022)
Dengue virus infection is caused by a dengue virus transmitted through mosquito bites from species Aedes albopictus and Aedes aegypti. The Ministry of Health takes action to reduce the prevalence of DHF by regulating the management of PSN 3M Plus. This study aimed to determine the knowledge, attitude, and compliance with the management of PSN 3M Plus strategies of those living in Surabaya. A cross-sectional population-based google form questionnaire was conducted in January 2022 for four weeks (January 3, 2022, to January 29, 2022). Based on the bivariate analysis, gender and age of respondents were no relationship between compliance with the PSN 3M Plus (p-value >0.05). The results also showed no relationship between education and adherence to PSN 3M Plus (p-value > 0.05). However, based on previous studies, people with higher education showed better compliance. Public knowledge and attitude about the dengue virus and its transmission process can be increased by developing, modifying, and intervening in the people controlling dengue virus infection. Most people of Surabaya believe that dengue prevention is the complete responsibility of every people. Based on the bivariate analysis, the characteristics of respondents had no relationship with the PSN 3M Plus compliance  (p-value > 0.05). Knowledge and attitudes of the Surabaya people toward PSN 3M Plus are still good. However, the characteristics of the respondents did not significantly affect their knowledge and attitudes